2012
DOI: 10.1371/journal.pone.0036378
|View full text |Cite
|
Sign up to set email alerts
|

Human Gastric Mucins Differently Regulate Helicobacter pylori Proliferation, Gene Expression and Interactions with Host Cells

Abstract: Helicobacter pylori colonizes the mucus niche of the gastric mucosa and is a risk factor for gastritis, ulcers and cancer. The main components of the mucus layer are heavily glycosylated mucins, to which H. pylori can adhere. Mucin glycosylation differs between individuals and changes during disease. Here we have examined the H. pylori response to purified mucins from a range of tumor and normal human gastric tissue samples. Our results demonstrate that mucins from different individuals differ in how they modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 40 publications
2
104
3
2
Order By: Relevance
“…In the present study, however, the in vitro capacities of H. heilmannii and H. ailurogastricus for binding to human gastric mucins were very low, and there was no difference in binding at low or neutral pHs. The binding capacities of H. heilmannii and H. ailurogastricus were 20-to 100-fold lower than the capacity of H. pylori for binding to the same human gastric mucins (42,52,54). Mucins can carry on the order of 100 different carbohydrate structures, which provide the mucins with a bottle brush appearance and make them act as receptors for microorganisms (55).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, the in vitro capacities of H. heilmannii and H. ailurogastricus for binding to human gastric mucins were very low, and there was no difference in binding at low or neutral pHs. The binding capacities of H. heilmannii and H. ailurogastricus were 20-to 100-fold lower than the capacity of H. pylori for binding to the same human gastric mucins (42,52,54). Mucins can carry on the order of 100 different carbohydrate structures, which provide the mucins with a bottle brush appearance and make them act as receptors for microorganisms (55).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either the mucus layer on HT29-MTX-E12 cells offered additional H. pylori receptors not present on the other cell lines or the mucus induced an alteration in adhesins produced by the organism that enabled interaction with the cells. Gastric mucins have been shown to promote the proliferation of H. pylori and to alter gene expression by the organism (58). Recently, we have shown that the interaction of H. pylori with the trefoil peptide TFF1, present in the adherent mucus layer of HT29-MTX E12 cells, promotes infection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Mucins can bind pathogens and can modulate bacterial growth, e.g., via stimulatory or inhibitory glycan motifs (17,18) and/or by being food sources for bacteria through released glycans (19). The ability of the mucin glycan structures to bind bacteria plays an important role in the mucosal defense against infection (15,20).…”
mentioning
confidence: 99%